Environmental Sustainability of Agricultural Farms in Bulgaria - BACHEV, Hrabrin; TERZIEV, Dimitar (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).02, 2018)
The issue of assessment of diverse aspects of sustainability of agricultural farms is among the most topical in the last decades. In Bulgaria, there are no comprehensive studies on environmental sustainability of farms in general or different types. This article applies a holistic framework for assessing environmental sustainability of Bulgarian farms. Initially the multiprinciple, multictiteria and mulriindicator framework for assessing environmental sustainability of farm in the country is outlined. After that a level of environmental sustainability of Bulgarian farms is evaluated in general and of farms of different juridical type, size, production specialization, and ecological and administrative location. Sustainability assessment is based on a first large-scale survey on environmental aspects of sustainability of agricultural farms in the country carried out in 2016. Third, relations between environmental and socio-economic and integral sustainability of Bulgarian farms are specified. Finally, factors for improving environmental and overall sustainability of agricultural farms in the country are identified. Our study has found out that environmental sustainability of Bulgarian farms is at a good level. Nevertheless, due to an inferior level of governance and economic sustainability the integral sustainability of Bulgarian farms is lower and the improvement of the latter two is critical for maintaining overall sustainability of Bulgarian farms at current stage of development.